Some concepts on Gondwana Landscapes: Long-term Landscape Evolution, Genesis, Distribution and Age - Rabassa, Jorge Oscar
The concept of “Gondwana Landscape” was defined by Fairbridge (The encyclopedia of geomorphology. Reinhold Book Corporation, New York, p. 483, 1968) as an “ancestral landscape” composed of “series of once-planed remnants” that “record traces of older planation” episodes during the “late Mesozoic (locally Jurassic or Cretaceous)”. This has been called the “Gondwana cyclic land surface” in the continents of the southern hemisphere, occurring extensively in Australia, Southern Africa and the cratonic areas of South America. Remnants of these surfaces are found also in India, and it is assumed they have been preserved in Eastern Antarctica, underneath the Antarctic ice sheet which covers that region with an average thickness of 3,000 m. These paleolandscapes were generated when the former Gondwana supercontinent was still in place and similar tectonic conditions in its drifted fragments have allowed their preservation. In Pangaea, remnants of equivalent surfaces, though of very fragmentary condition, have been described in Europe and the United States, south of the Pleistocene glaciation boundary. These Gondwana planation surfaces are characteristic of cratonic regions, which have survived in the landscape without being covered by marine sediments along extremely long periods, having been exposed to long-term subaerial weathering and denudation. Their genesis is related to extremely humid and warm paleoclimates of “hyper-tropical” nature, with permanently water saturated soils, or perhaps extreme climates, with seasonal and long-term cyclic fluctuations, from extremely wet to extremely dry. Deep chemical weathering is the dominant geomorphological process, with the development of enormously deep weathering profiles, perhaps of up to many hundreds of metres deep. The weathering products are clays, in some cases kaolinite, pure quartz and other silica types sands, elimination of all other minerals and duricrust formation, such as ferricretes (iron), silcretes (silica) and calcretes (calcium carbonate). Mean annual ...